Experimental Investigation on the Distribution Performance of Refrigerant Distributors - Han Qing; Zhang Chi; Xu Bo; Chen Jiangping (Zhileng xuebao)
Refrigeration mal-distribution in a distributor located at the inlet of a heater exchanger plays an important role in the heat exchanger performance. This paper proposes a test method to measure the mass flow rate and quality of each branch tube after distributor. Three types of distributors (pressure drop; centrifugal and reservoir) were manufactured and tested. It was found that with the increase of mass flow rate, the performance of distributor improved. The pressure drop and centrifugal type is more sensitive than reservoir one. With the increase of inlet quality, the performance of distribution deteriorates. The flow behavior of two-phase refrigerant such as phase distribution and separation phenomena was studied by CFD, which helped investigate how the geometry factors influence the distribution performance.